Marianne Novy. 2017. Shakespeare and feminist theory. Bloomsbury: London - Rayner, Francesca (2018)
[Excerpt] This volume on Shakespeare and Feminist Theory is a clear and accessible addition to the excellent Arden Shakespeare and Theory series. It is aimed on the one hand at university students of Shakespeare, or students of literature in general, who are interested in the ways in which feminist theory might illuminate analysis of the plays and, on the other, at university lecturers interested in integrating a module on feminist approaches to Shakespeare or even creating courses in Shakespeare and feminist theory. It is certainly a topical volume considering the range of feminist demands currently in the public sphere, from demands for greater representation and a highlighting of questions of sexual assault in the film industry to demands for equal pay for work of equal value across various sectors of the economy. Shakespeare and Feminist Theory does not explicitly mention these movements, but it does help to contextualize and theorise them and to apply feminist insights to representations of gender in Shakespeare’s plays. [...]